2020
DOI: 10.1089/cyber.2019.0482
|View full text |Cite
|
Sign up to set email alerts
|

Tablet and Smartphone or a Book: The Struggle Between Digital Media and Literacy Environment in Homes of Croatian Preschool Children and Its Effect on Letter Recognition

Abstract: The purpose of this study was to examine the relationships between the amount of time that preschool children, aged 6-7 years, spend using a tablet or a smartphone for entertainment purposes, aspects of their home literacy environment (HLE), and their letter recognition ability. Participants in the study were a convenient sample of 97 children (43 girls) aged 6-7 years and one of their parents, who agreed to participate in the research during the process of school readiness assessment. Children completed a let… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 26 publications
0
10
0
Order By: Relevance
“…Only six studies (23%) examined the nature of a child's smartphone or tablet use (Cho & Lee, 2017;Kotrla Topić et al, 2020;Levine et al, 2019;Lin et al, 2020;Neumann, 2014;Taylor et al, 2017). These studies generally found that smartphones and tablets were most commonly used for non-educational purposes including watching videos (Cho & Lee, 2017;Levine et al, 2019), entertainment (Kotrla Topić et al, 2020Taylor et al, 2017) and gaming (Neumann, 2014).…”
Section: Smartphone Tablet and Child-factor Measurementmentioning
confidence: 99%
“…Only six studies (23%) examined the nature of a child's smartphone or tablet use (Cho & Lee, 2017;Kotrla Topić et al, 2020;Levine et al, 2019;Lin et al, 2020;Neumann, 2014;Taylor et al, 2017). These studies generally found that smartphones and tablets were most commonly used for non-educational purposes including watching videos (Cho & Lee, 2017;Levine et al, 2019), entertainment (Kotrla Topić et al, 2020Taylor et al, 2017) and gaming (Neumann, 2014).…”
Section: Smartphone Tablet and Child-factor Measurementmentioning
confidence: 99%
“…Second, to exclude the influence of literacy knowledge, the current study only focused on screen time for entertainment purposes. However, screen time for learning purposes has been shown to account for a substantial part of children’s use of digital devices (Kotrla Topić et al, 2020 ; Sousa & Rocha, 2019 ). Investigations of screen time for learning purposes could deepen our understanding of the mechanisms of the role of screen time for different purposes in the BOI effect with children.…”
Section: Discussionmentioning
confidence: 99%
“…The parents’ education levels were measured on a 7-point scale: 1 = third grade or below, 2 = fourth grade to sixth grade, 3 = middle school, 4 = high school, 5 = college school, 6 = university, 7 = postgraduate. As well, the parents were asked to answer a question about the time (in minutes) their children spent using digital devices for entertainment purposes (e.g., playing games, searching the Internet, watching videos, or visiting social networks) on a typical day (Kotrla Topić et al, 2020 ; Neumann, 2018 ).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations